Geometrical and electrical predictors of cardiac resynchronization therapy response. (July 2014) - Stabile, Giuseppe; Iuliano, Assunta; La Rocca, Vincenzo; Solimene, Francesco; Fazio, Roberta; De Simone, Antonio
<x xml:space="preserve">Abstract</x> Several studies have demonstrated the beneficial effect of cardiac resynchronization therapy (CRT) in patients with drug-refractory heart failure. A variable proportion, up to 30%, of CRT patients do not benefit from treatment. The lack of response to CRT has a variety of potential causes. The implantation process is fundamental to the success of CRT, since little can subsequently be done to improve the CRT response. The authors reviewed all the geometrical and electrical parameters that could guide the CRT implant and predict its response.